A comparison between Malay and Chinese ethnics in Kuching North City / Mohamed Faizal Shah Ali - Ali, Mohamed Faizal Shah (2007)
Children influence and interaction with their parents happens everyday and almost in every situation. The main focus of this research is to study the nature of children-parents interaction and influence in parent’s purchasing decision between Malay and Chinese ethnics in Kuching North City area.